Retrospective Review of Patients Operated on with Bilateral Cleft Lip through Surgical Outreaches in Kenya. (15th April 2013) - Nangole, F. W.; Khainga, S. O.
Abstract : This was a study to evaluate the characteristics and outcome of patients operated on with bilateral cleft lip through surgical outreach programs in Kenya between January 2006 and December 2011. Files for fifty-nine patients operated on during the study period were evaluated. The mean age for surgery was ten months with about forty-five percent of the patients more than one year of age. No presurgical orthopaedic devices were utilized on any of the patients. Mulliken surgical technique and the Manchester technique were the commonest surgical techniques in equal proportions. An overall complication rate of about 7.5 percent was noted. In conclusion we noted a delay in the surgical management of the majority of our patients. This resulted in a backlog of cases. There is thus a need to intensify more surgical outreach camps as well as training more surgeons to assist in the management of clefts. Cleft surgery is a relatively safe surgery that could be carried out in relatively remote centers through surgical outreach programs. This was evidenced by the low complication rates in our series.